Enhancing Recovery in Gastrointestinal and Cardiovascular Surgeries through ERAS Protocols - Faisal Toheed, Syed Shaukat Ali Shah, M. Subhan Shahid, Sana Ullah Malik, Ayesha Majeed, Nawaz Ali Dal, Afshan Nafees, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Enhanced Recovery After Surgery (ERAS) protocols are evidence-based, multimodal perioperative care pathways designed to reduce surgical stress, accelerate recovery, and improve clinical outcomes. While ERAS has been widely implemented in gastrointestinal surgery, its application in cardiovascular surgery remains limited, particularly in resource-constrained healthcare settings. Objective: To evaluate the effectiveness of ERAS protocols in improving postoperative recovery outcomes among patients undergoing gastrointestinal and cardiovascular surgeries at tertiary care hospitals. Methods: This multicenter prospective observational study included 120 adult patients undergoing elective gastrointestinal and cardiovascular surgeries at THQ Hospital, Ali Pur, Muzaffargarh, and Services Hospital, Lahore, from June 2022 to April 2023. Patients were managed either under ERAS-based perioperative care or conventional perioperative protocols. Data were collected on demographic characteristics, recovery milestones, postoperative complications, length of hospital stay, opioid consumption, and readmission rates. Statistical analysis was performed using SPSS version 26, with a p-value of <0.05 considered statistically significant. Results: Patients managed with ERAS protocols demonstrated significantly earlier initiation of oral intake and mobilization compared with conventional care (p < 0.001). The ERAS group showed a lower overall postoperative complication rate (18.3% vs. 36.7%, p = 0.03), reduced duration of mechanical ventilation and intensive care unit stay in cardiovascular surgery patients, and a significantly shorter mean hospital stay (5.6 ± 1.9 days vs. 8.9 ± 2.7 days, p < 0.001). Opioid requirements were significantly reduced in the ERAS group, with no significant difference in 30-day readmission rates. These benefits were observed consistently across both male and female patients. Conclusion: Implementation of ERAS protocols significantly enhances postoperative recovery in gastrointestinal and cardiovascular surgeries by reducing complications, shortening hospital stay, and promoting early functional recovery without compromising patient safety. Adoption of ERAS pathways in tertiary care hospitals may improve surgical outcomes and optimize healthcare resource utilization. Keywords: Enhanced Recovery After Surgery, ERAS, Gastrointestinal Surgery, Cardiovascular Surgery, Perioperative Care, Postoperative Outcomes.